Optical Coherence Tomography Angiography of Iris Nevus: A Case Report - Allegrini, Davide (Case Rep Ophthalmol, 2016)
Iris nevus is common: 6% of patients with suspected iris melanoma have lesions other than melanoma, and 36% of them are nevi. Iris nevus turns into melanoma in approximately 8% of cases at a mean of 15 years. This case report provides the first description of an iris tumor examined with iris optical coherence tomography angiography (OCTA) compared to iris fluorescein angiography (IFA). A 60-year-old man with a diagnosis of iris nevus in the left eye was referred to our department for IFA and iris OCTA. The iris vasculature in IFA was visible only in the early phases, but not clearly. OCTA, however, gave visualization of the vascular network and very precisely defined the vessels of the whole lesion, except for the pupillary portion, which was masked by superficial pigment accumulations. IFA and iris OCTA can add information about the vascular architecture compared to slit-lamp biomicroscopy, ultrasound biomicroscopy, and anterior-segment OCT. However, IFA is time-consuming and invasive and can – very occasionally – cause serious adverse reactions. In contrast, OCTA defines the texture of the iris vasculature better. In conclusion, OCTA is a new method, easy to execute, needing no dye injection, and provides useful information on the vascular network of iris lesions. It could therefore be helpful in the diagnosis and follow-up of these lesions.